2014
DOI: 10.1016/j.proeng.2014.12.236
|View full text |Cite
|
Sign up to set email alerts
|

Study On the Relationship between Surface Roughness of AA6061 Alloy End Milling and Image Texture Features of Milled Surface

Abstract: The Surface roughness and image texture features of milled surfaces are key parameters to study the surface characteristics of end milled AA 6061 alloy. A Machine vision system is employed to capture and store the images of the end milled workpieces.The stylus type instrument is used measure the surface roughness values of various milled workpieces for different cutting conditions such as speed, feed and depth of cut.The Grey Level Cooccurance Matrix [GLCM] is introduced to extract the image texture features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…After the capture of the image, it is necessary to improve the quality of the same and the errors of distortion depending on the type of analysis desired. For this purpose, there are some operations of pre-processing such as: morphological, subtraction and filtering [26,27].…”
Section: Image Processing Techniquesmentioning
confidence: 99%
“…After the capture of the image, it is necessary to improve the quality of the same and the errors of distortion depending on the type of analysis desired. For this purpose, there are some operations of pre-processing such as: morphological, subtraction and filtering [26,27].…”
Section: Image Processing Techniquesmentioning
confidence: 99%
“…The results demonstrated that the highest correlation of investigated features and surface roughness was reached at angles 0° and 180° except for the feature named "correlation" generated from GLCM matrix which had the highest correlation with surface roughness at an angle of 90°. Different from the workpiece inclination (X-Z plane) and workpiece orientation (X-Y plane) authors in the paper [7] investigate direction (0°, 45°, 90° and 135°) of GLCM matrix generation at constant distance between pixels and its influence on the correlation of features extracted from GLCM matrix and surface roughness. Surface texture features based on a digital image GLCM matrix are not used for the surface roughness evaluation and description only.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen element feature vector obtained from the captured images from end milled and turning process was used for analysis. The Grey Level Co-occurrence Matrix is utilized to separate the features of the end milled surface texture images by Nathan et al [22].…”
Section: Introductionmentioning
confidence: 99%